21st century Power : strategic superiority for the modern era (21st century foundations, 2018)
"This book uses the 21st Century Foundations series format to re-introduce the writings of General Thomas S. Power, the third Commander-in-Chief of the Strategic Air Command (SAC). His unappreciated works contain insights into military topics such as technology and the arms race, the nature of deterrence, and the military utility of space."--Provided by publisher.